2013
DOI: 10.1590/s1517-86922013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do percentual de gordura obtido por bioimpedância, ultrassom e dobras cutâneas em adultos jovens

Abstract: Introductions e objective: To compare portable ultrasound (US) and bioimpedance analysis (BIA) with skinfolds (SF) to estimate body fat percentage in adults. Methods: 195 military men were assessed and they had their weight, height, body fat by bioimpedance, skinfold in 9 points and ultrasound (US) collected. linear regression was used for the development of a new equation for body fat percentage estimation in young adults (males). results: The group had mean age of 23.07 ± 7.55 years and height and weight wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
4
16
0
6
Order By: Relevance
“…A study conducted by Neves et al, 13 in the city of Curitiba, evaluated a sample of 195 military personnel from the EB, mean age of 23.1 (± 7.6) years, and found a mean fat percentage of 14.6 ± 6.4)%, values close to those found in the present study. In another study in a sample of 92 soldiers, with a mean age of 20 (± 1.8) years, performed by Botelho et al, 14 the percentage of fat obtained was 13.8 (± 5.1)%.…”
Section: Discusionsupporting
confidence: 88%
“…A study conducted by Neves et al, 13 in the city of Curitiba, evaluated a sample of 195 military personnel from the EB, mean age of 23.1 (± 7.6) years, and found a mean fat percentage of 14.6 ± 6.4)%, values close to those found in the present study. In another study in a sample of 92 soldiers, with a mean age of 20 (± 1.8) years, performed by Botelho et al, 14 the percentage of fat obtained was 13.8 (± 5.1)%.…”
Section: Discusionsupporting
confidence: 88%
“…For this research, the 7‐site option was the chosen, since previous research indicated that equations using more anatomic points tended to be more precise for estimating BF%. The 9‐site option was not adopted because of the lack of studies indicating its reliability 3 , 9 . For each evaluation, at least 2 measurements were made at each point, with the possibility of performing a third one in cases of software requests due to discrepancies in the 2 previous measurements.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 This technology may present imprecise data as a result of recent physical activity or alcohol consumption, on the same day or on the days before the exam, for example. 5 It is common the estimation of equations aiming to predict BF%, with low-cost variables such as the skinfold method and body circumferences (BC), using DXA or BIA as a parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Among the anthropometric indicators of lower cost and faster implementation, the body mass index (BMI) is a highly used simple equation (body mass/stature²) that classifies individuals as underweight, normal weight, overweight and obesity I, II and III 5 . Although high BMI has already been correlated with risk of arterial hypertension, 1,6 the method is limited because it does not differentiate lean body mass and fat mass in its calculation, making it difficult to use it as a predictive value of body fat percentage BF% and abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%